2011
DOI: 10.1176/ps.62.6.pss6206_0619
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Postpartum Depression Care Among Low-Income Women

Abstract: Objective-The goal of this study was to characterize racial-ethnic differences in mental health care utilization associated with postpartum depression in a multiethnic cohort of Medicaid recipients.Methods-In a retrospective cohort study, administrative claims data from New Jersey's Medicaid program were obtained for 29,601 women (13,001 whites, 13,416 blacks, and 3,184 Latinas) who delivered babies between July 2004 and October 2007. Racial-ethnic differences were estimated with logistic regression for initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(115 citation statements)
references
References 53 publications
(18 reference statements)
4
110
0
1
Order By: Relevance
“…Among blacks, the higher prevalence of poverty, racism, low education, diagnostic and treatment bias (Nelson et al 2002) may contribute to observed racial disparity in suicidal behavior. Additionally, black women had higher prevalence of prenatal depression (Orr et al 2006), but were less likely to initiate treatment and receive follow-up treatment among those who initiate treatment (Kozhimannil et al 2014). Observed racial differences in suicide and suicidal behavior will have important implications in suicide prevention efforts given that one of the core objective of the Patient Protection and Affordable Care Act is reducing racial disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Among blacks, the higher prevalence of poverty, racism, low education, diagnostic and treatment bias (Nelson et al 2002) may contribute to observed racial disparity in suicidal behavior. Additionally, black women had higher prevalence of prenatal depression (Orr et al 2006), but were less likely to initiate treatment and receive follow-up treatment among those who initiate treatment (Kozhimannil et al 2014). Observed racial differences in suicide and suicidal behavior will have important implications in suicide prevention efforts given that one of the core objective of the Patient Protection and Affordable Care Act is reducing racial disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Many mothers are reluctant to seek treatment, and those who do are often reticent to disclose their symptoms to health care providers (Abrams & Curran, 2009; CDC, 2008;Ko, Farr, Dietz, & Robbins, 2012), particularly women from diverse cultures (Dennis & Chung-Lee, 2006;Kozhimannil, Trinacty, Busch, Huskamp, & Adams, 2011). Because many of the symptoms of postpartum depression mimic signs of pregnancy including fatigue, anxiety, and irritability, many providers are hesitant to screen for depression (Seehusen, Baldwin, Runkle, & Clark, 2005).…”
Section: Working With Mothers Who Have Postpartum Depressionmentioning
confidence: 99%
“…In particular, clinicians can increase use of the postpartum visit as gateway to interconception care, identify women who had adverse outcome in pregnancy and enhance care plans, and use evidence-based and best practices with a particular focus on effective contraceptive methods, 48 managing diabetes 49,30 reducing weight 50,51 smoking cessation 52,53 and psychosocial risk factors. [54][55][56][57] r e f e r e n c e s…”
Section: Postpartum Visits As a Gateway To Interconception Carementioning
confidence: 99%